Procesowa orientacja przedsiębiorstw : wyniki badań empirycznych - Cieśliński, Wojciech (Business Process Orientation : Empirical Research Results, 2009)
The purpose of this research was to diagnose the development of process orientation in companies, The development of process orientation is determined by three factors: firstly - the willingness to implement the quality management system, secondly - the implementation of effectiveness improvement programmes, thirdly - the implementation of knowledge management built-in systems. It has been indicated that the catalyst of the process orientation dynamic development, from the start through the growth to perfection, is the keenness to improve the company's organizational effectiveness, and the inhibitor is the instrumental approach to implement the quality systems and knowledge management built-in systems. In the paper, the methodology of diagnosing phases of companies' process maturity development has been shown, as well as the case study. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 41-48